Past pandemics and their parallel situation in Nepal - Pokharel, Jiba Raj (Applied Science and Technology Annals, 2020)
Pandemics have been occurring in the world since time immemorial. It is difficult in the case of the ancient pandemics but pandemics of later origin have conveyed some messages or the other. These are valuable lessons which should be accepted wholeheartedly for facing more competently in the following pandemics. This article deals with the pandemics that have hit the world since early times. It also portrays the situation that was prevailing in Nepal during the time of the pandemic. It has been found that Nepal did not have connectivity with the pandemics in the past. It is only in the Corona pandemic that Nepal has also been a part of the whole globe. Nepali people considered the diseases were thrown upon people by God because of the grave mistakes committed by them due to lust and greed. So, people worshipped God instead of making a scientific inquiry in this field. Even though, Ayurvedic medicines based on local herbs and the likes were produced and used in the case of the pandemics.